2005
DOI: 10.1158/0008-5472.can-04-3497
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor–Binding Fragment–Associated Antigen 9 Is a Tumor-Promoting and Prognostic Factor for Renal Cell Carcinoma

Abstract: The estrogen receptor-binding fragment-associated antigen 9 (EBAG9) has been identified as a primary estrogenresponsive gene in human breast cancer MCF7 cells. A high expression of EBAG9 has been observed in invasive breast cancer and advanced prostate cancer, suggesting a tumorpromoting role of the protein in malignancies. Here we show that intratumoral (i.t.) administration of small interfering RNA against EBAG9 exerted overt regression of tumors following s.c. implantation of murine renal cell carcinoma (RC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 27 publications
(33 reference statements)
1
43
0
Order By: Relevance
“…Expression of EBAG9, which is homologous to RCAS1, reportedly was correlated with in vivo tumor growth. 18 However, no apparent association between EBAG9 expression and in vitro cell growth was observed. Because the number of infiltrating CD8-positive T lymphocytes decreased in tumors composed of EBAG9-overexpressing cells in vivo, it is possible that immunosurveillance status may be suppressed by EBAG9 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of EBAG9, which is homologous to RCAS1, reportedly was correlated with in vivo tumor growth. 18 However, no apparent association between EBAG9 expression and in vitro cell growth was observed. Because the number of infiltrating CD8-positive T lymphocytes decreased in tumors composed of EBAG9-overexpressing cells in vivo, it is possible that immunosurveillance status may be suppressed by EBAG9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the murine renal cell carcinoma cell line RenCa, which harbors EBAG9 in BALB/c nude mice, had tumor growth potential similar to that of RenCa cells, which expresses vector alone. 18 The discrepancy between these 2 studies is unclear. However, other cell lines, including the endometrial cancer Hec-1 cells and Ishikawa cells, also formed larger tumors in nude mice after the RCAS1-encoding gene was introduced (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several researchers have suggested a potential link between advanced malignancy and high-level expression of EBAG9 in tumor tissue (3,(23)(24)(25)(26)(27)(28), evidence that this molecule itself exerts an in vivo tumor-promoting function has been lacking. Recently, Ogushi et al reported for the first time that the enhanced expression of EBAG9 in Renca mouse renal cancer cells leads to accelerated in vivo cell growth, using two representative clones generated by transfection of a human EBAG9 cDNA (12). Importantly, they also demonstrated in the same Renca-BALB/c model that the repression of endogenous EBAG9 expression, using RNA interference technology, slows tumor growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ogushi et al demonstrated that the overexpression of EBAG9 in a murine renal carcinoma cell line enhanced in vivo tumorigenesis, providing the first evidence of a tumorpromoting function for EBAG9 (12 involvement of an immune-evasion mechanism in the observed effect mediated by EBAG9, but did not describe whether this overexpressed EBAG9 protein was localized on the cell surface or at the Golgi membrane to exert tumor promotion (12).…”
Section: Introductionmentioning
confidence: 99%